2003
DOI: 10.2174/0929867033456387
|View full text |Cite
|
Sign up to set email alerts
|

[General Articles] Cannabinoids: Mechanisms and Therapeutic Applications in the CNS

Abstract: Cannabinoids comprise three classes of compounds, the active components of marijuana (Cannabis sativa), as well as endogenous and synthetic derivatives. To date, two distinct cannabinoid receptors (CB1 and CB2) have been discovered, but evidence for further receptor types has been brought forward. The potential use of cannabinoids for medicinal purposes has long been known, but the mechanisms of action of both exogenously applied and endogenous cannabinoids are only partly established. For nervous system disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Neurotoxicity and Neurotrauma. The endocannabinoid system plays an important role in neuroprotection both in acute neuronal injury (e.g., traumatic brain injury, stroke, and epilepsy) and in chronic neurodegenerative disorders, such as multiple sclerosis, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, and Alzheimer's disease (reviewed in Glass, 2001;Mechoulam et al, 2002a,b;Grundy, 2002;Croxford, 2003;Drysdale and Platt, 2003;Jackson et al, 2005a;Ramos et al, 2005). Although the underlying mechanisms are not fully understood, multiple cannabinoid receptor-dependent as well as receptor-independent processes have been implicated.…”
Section: Central Nervous System Disordersmentioning
confidence: 99%
“…Neurotoxicity and Neurotrauma. The endocannabinoid system plays an important role in neuroprotection both in acute neuronal injury (e.g., traumatic brain injury, stroke, and epilepsy) and in chronic neurodegenerative disorders, such as multiple sclerosis, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, and Alzheimer's disease (reviewed in Glass, 2001;Mechoulam et al, 2002a,b;Grundy, 2002;Croxford, 2003;Drysdale and Platt, 2003;Jackson et al, 2005a;Ramos et al, 2005). Although the underlying mechanisms are not fully understood, multiple cannabinoid receptor-dependent as well as receptor-independent processes have been implicated.…”
Section: Central Nervous System Disordersmentioning
confidence: 99%
“…For example, the inhibitory effects of cannabinoids on the excitotoxic neurotransmitter glutamate (Drysdale & Platt, 2003) and their capacity to counter the oxidative damage to dopaminergic neurones has raised the possibility that they may be of value in the treatment of At the neuronal level low doses of cannabinoids can elevate intracellular calcium levels and increase transmitter release (Sarne & Keren, 2004). Doble and coworkers note that intracellular calcium plays a key role in mediating neuronal cell death (Doble, 1999;Hubert & Doble, 1998).…”
Section: Edge Hill College Of Higher Educationmentioning
confidence: 99%
“…For example, the inhibitory effects of cannabinoids on the excitotoxic neurotransmitter glutamate (Drysdale & Platt, 2003) and their capacity to counter the oxidative damage to dopaminergic neurones has raised the possibility that they may be of value in the treatment of Parkinson's disease (Croxford, 2003). In terms of their effects on cell survival, human and animal studies have revealed that cannabinoids can be either neurotoxic or neuroprotective (Guzman et al 2001).…”
mentioning
confidence: 99%
“…⌬ 9 -THC, the primary psychoactive ingredient of marijuana, has been available for several years in an oral form (Marinol) for treatment of nausea and vomiting associated with cancer chemotherapy and for use in loss of appetite and weight loss related to AIDS. Additionally, cannabinoids may be useful in treating neurological/movement disorders, chronic pain, glaucoma, in neuroprotection, as well as other disease states (for recent review, see Baker et al, 2003;Croxford, 2003;Drysdale and Platt, 2003). There are also many unanswered questions about the negative consequences of long-term marijuana consumption or use of cannabinoid therapeutics, particularly when it comes to the issues of dependence liability and the possibility of long-term cognitive deficits.…”
mentioning
confidence: 99%